ANALISIS RENCANA PENGEMBANGAN HUTAN TANAMAN DI WILAYAH KPHP MODEL SINTUWU MAROSO DESA LEBONI KECAMATAN PAMONA PUSELEMBA KABUPATEN POSO - Tudjuka, Sullu Elyakim; Hamzari, Hamzari; Golar, Golar (Universitas Tadulako, 2015)
Nowadays, some part of KPHP model Sintuwu Maroso areal, Poso has destroyed that caused by human activities such as illegal logging and land conversion for plantation. A good planning of forest use with purpose to increases income of the local community is needed to solve that problems. The aim of this study was to know biophysics condition, social-economic of community and suitability of the planning of community forest development. The research was conducted at KPHP Model Sintuwu Maroso, the village of Leboni, Poso Regency, Central Sulawesi, from April through June 2014. This study uses a survey method, where primary and secondary data were collected by using questionnaires and in-depth interviews on respondents. The total number of respondent swere ten. Respondents were determined byusing snowball sampling method, withthe consideration that they are local communities and member of farmer group. Analysis wasdone by description method and comparison between planning of KPHP and results of this study. Planning on the development of plantation forest was aimed to empower the local communities, regarding to push focuses their attention to conserve the forest area. The development of plantation forest with rubber (Heveabrassiliensis) is decided correct because it is compatible with biophysics condition, while it was gave ecology and economic benefits. Keywords: Analysis, Planning, Development, Plantation Forest, KPHP.